Effect of helium on structure and compression behavior of SiO(2) glass - Shen, Guoyin (National Academy of Sciences, 2011)
The behavior of volatiles is crucial for understanding the evolution of the Earth’s interior, hydrosphere, and atmosphere. Noble gases as neutral species can serve as probes and be used for examining gas solubility in silicate melts and structural responses to any gas inclusion. Here, we report experimental results that reveal a strong effect of helium on the intermediate range structural order of SiO(2) glass and an unusually rigid behavior of the glass. The structure factor data show that the first sharp diffraction peak position of SiO(2) glass in helium medium remains essentially the same under pressures up to 18.6 GPa, suggesting that helium may have entered in the voids in SiO(2) glass under pressure. The dissolved helium makes the SiO(2) glass much less compressible at high pressures. GeO(2) glass and SiO(2) glass with H(2) as pressure medium do not display this effect. These observations suggest that the effect of helium on the structure and compression of SiO(2) glass is unique.